The Ideological-Programmatic Coherence of the Political Parties in Chile and Mexico: To What Extent and Why Do the Ideological Position of the Parliamentary Members Match with the Content of the Electoral Programs? - Martínez-Hernández, Aldo Adrián; Miranda Olivares, Nicolas (Revista de Ciencia Política, 2020)
This research develops a method for the study of the ideological-programmatic coherence of political parties. It designs tools for the spatial analysis of the distance between the formal ideology of a party—as determined by the content of its electoral platform—and the ideological positions that its legislative representatives attribute to their own party organization. To do this, we analyze political parties in Chile and Mexico, with the purpose of determining the differences between parties and coalitions in different systems. The research concludes that coalitions and parties located on the right of the political spectrum are less coherent than those located on the left—a feature that is most evident in the context of coalition governments.